Thermal Resistance Analysis and Numerical Optimization of Mechanical Expanded Tube-to-Fin Joints - Li Sisi; Ouyang Xinping; Xia Rongxin; Li Donglei (Zhileng xuebao)
The finite element simulation method was used to obtain the distribution of contact stress between the fin and the base pipe. It is proposed that the overall contact stress is not just the average value of the node contact stress, and a more reasonable method of calculation method is proposed. A heat transfer performance test of a sleeve-type heat exchanger was undertaken to determine the contact thermal resistance between the fin and the base pipe. The correlation between the overall contact stress and the contact thermal resistance was established. The finite element simulation method was used to determine the overall contact stress under various expansion factors, and to determine the optimal process dimension. Finally, the contact stress value calculated by the elastoplastic theory was used for internal verification. The relative deviation between the contact stress calculated using elastoplastic theory and the simulated value was small (7.3%).